An investigation of the Steady-State and Fatigue Problems of a Small Wind Turbine Blade Based on the Interactive Design Approach - Khalil Deghoum; Mohammed T Gherbi; Muhsin J Jweeg; Hakim S Sultan; Azher M Abed; Oday I Abdullah; Necib Djilani (International Journal of Renewable Energy Development, 2023)
A wind turbine blade is an essential system of wind energy production. During the operation of the blade, it is subjected to loads resulting from the impact of the wind on the surface of the blade. This leads to appear large deflections and high fatigue stresses in the structure of blades. In this paper, a 5 kW horizontal axis wind turbine blade model is designed and optimized using a new MATLAB code based on blade element momentum (BEM) theory.The aerodynamic shape of the blade has been improved compared with the initial design, the wind turbine power has been increased by 7% and the power coefficient has been increased by 8%.  The finite Element Method was used to calculate the loads applied to the blade based on Computational Fluid Dynamics (CFD) and BEM theory.High agreements were obtained between the results of both approaches (CFD and BEM).The ANSYS software was also used to simulate and optimize the structure of the blade by applying variable static loads 3.3, 6, and 8.3 kg and compared the results with the experimental results. It was reduced the maximum deflectionswith 37%, 42.85%, and 42.61% when using CFRP material and 4.5%, 15.45%, and 16.19% for GFRP material that corresponds to the applied forces. Based on the results, the mass of the optimized model decreased by 47.86% for GFRP and 71.24% for CFRP. IEC 61400.2 standard was used to estimate thefatigue loads, damage, blade life prediction, and verify blade safety usinga Simplified Load Model(SLM) and FAST software. It was found that the blade will be safe under extreme wind loads, and the lifetime of the wind blade (GFRP) is 5.5 years and 10.25 years,according to SLM and FAST software, respectively. At the same time, the lifetime of the wind blade (CFRP)is more than 20 years, according to the two applied methods.